'A Vast Intellectual Fusion ... of the Various National Tendencies': Goethe and Henry James. (March 2014) - Adler, Jeremy
<x content-type="archive" xml:space="preserve">Abstract</x> It has largely escaped attention that Goethe played a major part in shaping the fiction of Henry James. James's appreciation of Goethe is apparent from many statements, especially his fine review of Carlyle's translation of Wilhelm Meister. From his first novel, Watch and Ward, via the great novel of his middle period, The Portrait of a Lady, to one of the major novels of his late phase, The Ambassadors, James varied the Goethean Bildungsroman. Other Goethean elements that James adopts include the ideas of Weltliteratur, the notion of organic form and the theme of 'life'.